Micromycetes of rhizosphere and phillosphere in the lines of wheat (Triticum aestivum L.) isogenic by VRN in relation to the development rate and productivity - Avksentyeva, O.; Vinnikova, O. (The Journal of V.N.Karazin Kharkiv National University. Series «Biology», 2018)
The field experiments were performed in order to assess the micromycetes number and species composition in the rhizosphere and phillosphere of the Myronivska 808 soft wheat lines isogenic by VRN genes in relation to the rate of wheat development. It was established that the lines with dominant genes VRN-A1a and VRN-D1a came to the earing phase remarkably earlier than the line with the dominant gene VRN-B1a. In lines, which have faster development, the parameters of individual productivity were higher, and the content of protein in grains was lower than that in the line with lower development rate. The number of micromycetes species and their propagules in the rhizosphere of all wheat lines were higher than that in the phillosphere. As a result of the study of species diversity of NILs mycocenoses from rhizosphere of wheat 319 strains of micromycetes, belonging to 20 genera of Zygomycota and Ascomycota, were isolated in pure culture. The most species were identified from genera Fusaruim, Aspergillus, Рenicillium, Trichoderma, Mucor, and dark-pigmented micromycetes. It was established that in the rhizosphere the maximum number of micromycetes species and propagules was associated with the isolines of VRN-A1a and VRN-D1a, which showed an accelerated development, while the minimum fungi diversity occurred in the root soil of the VRN-B1a line. The phillosphere of the plant ears in all studied wheat isolines appeared to be rather poor in microscopic fungi: only 27 strains belonging to 6 genera were identified. Potential phytopathogens – representatives of the genus Fusarium were found on the surface of the plant ears of all lines, and in the phillosphere of plants of VRN-A1a line there were also representatives of dark pigmented micromycetes. The number of fungal propagules was also maximal for isolines with accelerated rates of development – VRN-A1a and VRN-D1a, and minimal for plants of VRN-B1a isoline. Thus, population density of micromycetes and their species structure, both in rhizosphere and on plant ears, correlated with the rate of development of wheat lines, which was determined by the dominant/recessive state of the VRN genes. Therefore it can be assumed that VRN genes are indirectly involved in the formation and functioning of the mycosenoses of the studied isogenic lines of soft wheat, particularly via their participation in the regulation of physiological and biochemical processes.